A longitudinal study on students’ self-regulated listening during transition to an English-medium transnational university in China - Zhou , Sihan; Thompson, Gene (Studies in Second Language Learning and Teaching, 2023)
Listening to academic content in English medium instruction (EMI) classrooms at university can be a demanding task for students who transition from first language (L1) instructed secondary schools. This longitudinal mixed methods study analyzes data from 316 students collected at the beginning, midterm, and the end of their first semester after entering an EMI transnational university in southeast China. The analysis of questionnaire responses revealed significant variations in students’ listening strategies over time, with a significant decrease in deep processing cognitive strategies at the midterm when content difficulty increased. Conversely, two types of metacognitive strategies (problem solving, plan evaluation) increased significantly during the second half of the semester. Informed by Zimmerman’s (2000) social cognitive self-regulated learning (SRL) model, thematic analysis of semi-structured interviews with 34 participants revealed that students generally developed a more top-down listening approach focusing on content learning over the semester and became more selective in their strategic and self-regulatory processes after the midterm “watershed” moment. Results highlight the importance of structured topic knowledge in EMI curriculum design and the necessity of strategy training in language support programs.